INTERNALISASI NILAI TEPUK SAKINAH DALAM MEMBANGUN KEHARMONISAN KELUARGA: STUDI PADA PASANGAN BARU MENIKAH DI JEMBER - Abdurrahman Mahmud; Emha Aminullah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study investigates the implications of Tepuk Sakinah premarital education for family harmony among newly married couples in Jember City. Employing a qualitative approach with a case study design, data were obtained through in-depth interviews with couples who had attended premarital counseling programs and were analyzed using thematic analysis. The results reveal that Tepuk Sakinah does not merely serve as an ice-breaking activity, but functions as a medium for internalizing core Islamic marital values, namely zawaj, mitsaqan ghaliza, mu’asyarah bil ma’ruf, deliberation (musyawarah), and tarāḍhīn. These values are internalized in early marital life through dialogical communication, emotional bonding, heightened awareness of marital commitment, and mutual acceptance of spousal differences. The primary implication of this internalization is the strengthening of family harmony, which is conceptualized not as the absence of conflict, but as couples’ ability to manage relational dynamics and conflicts constructively. The novelty of this study lies in demonstrating that a symbolic and participatory premarital education method, integrated with a meaningful communication (deep talk) approach, can generate sustainable effects on early marital relationships. This study underscores the need to develop premarital education models that are communicative, contextual, and grounded in religious values